Enantioselective formation and ring-opening of epoxides catalysed by halohydrin dehalogenases. (20th March 2006) - Janssen, D.B.; Majerić-Elenkov, M.; Hasnaoui, G.; Hauer, B.; Spelberg, J.H. Lutje
Abstract : Halohydrin dehalogenases catalyse the conversion of vicinal halohydrins into their corresponding epoxides, while releasing halide ions. They can be found in several bacteria that use halogenated alcohols or compounds that are degraded via halohydrins as a carbon source for growth. Biochemical and structural studies have shown that halohydrin dehalogenases are evolutionarily and mechanistically related to enzymes of the SDR (short-chain dehydrogenase/reductase) superfamily. In the reverse reaction, which is epoxide-ring opening, different nucleophiles can be accepted, including azide, nitrite and cyanide. This remarkable catalytic promiscuity allows the enzymatic production of a broad range of β-substituted alcohols from epoxides. In these oxirane-ring-opening reactions, the halohydrin dehalogenase from Agrobacterium radiobacter displays high enantioselectivity, making it possible to use the enzyme for the preparation of enantiopure building blocks for fine chemicals.